Melanoleuca subgriseoflava and M. substridula—two new Melanoleuca species (Agaricales, Basidiomycota) described from China - Yue Qi; Cai-Hong Li; Yu-Meng Song; Ming Zhang; Hong-Bo Guo; Xiao-Dan Yu (PeerJ, 2022)
Two new Melanoleuca species, Melanoleuca subgriseoflava and M. substridula, are originally reported and described in China based on both morphological and molecular methods. Melanoleuca subgriseoflava, collected in Liaoning province, is mainly characterized by its greyish-brown to yellowish-grey pileus, creamy to light orange lamellae, greyish-yellow context, round and warted basidiospores and fusiform hymenial cystidia. Melanoleuca substridula, discovered in Sichuan province, is mainly characterized by its light brown to dark brown pileus, whitish lamellae, light brown to greyish-brown stipe, round and warted basidiospores and lack of any forms of cystidia. The phylogenetic relationships as well as divergence-time estimation were analyzed using the combined data set (ITS-nrLSU-RPB2), and the results showed that the two Melanoleuca species formed two distinct lineages. Based on the combination of morphological and molecular data, M. subgriseoflava and M. substridula are confirmed as two new species to science. A theoretical basis is provided for the species diversity of Melanoleuca.